The impact of CEO compensation on financial reporting quality - LUO, MINYI (2017)
This study investigates the impact of CEO compensation on financial reporting quality. Using a sample of 1,500 listed U.S. firms, fiscal years from 2008 to 2016, I find that the percentage of CEO salary has a significantly negative association with the measure of financial reporting quality, the absolute value of the abnormal accruals (divided by total asset). In contrast, the percentage of CEO bonus and values of stock options are positively related to the abnormal accruals. This paper suggests that salary as a component of CEO compensation promotes high financial reporting quality but the CEO bonus and stock options lower the financial reporting quality.